Also Intransitive. Mark Fisher's Hauntology. Issue 3 (December 2020) - Gildea, Niall
Abstract : This article offers a reading of the version of Jacques Derrida's concept of 'hauntology' that is developed by Mark Fisher in his essay collection, Ghosts Of My Life: Writings on Depression, Hauntology and Lost Futures . The article begins by noting some salient genealogical features of Fisher's critique of Derrida, and argues that Fisher's engagement with hauntology prompts an elaboration of Fisher's thinking about Derrida which corresponds to the elaboration in Derrida's thinking which, for Fisher, hauntology marks. But it also goes on to suggest, in a manner that is intended to pay tribute to Fisher's final work, The Weird and the Eerie, that Fisher's engagement with Derrida has a weird performativity, irreducible (as always in Fisher) to mere commentary or exegesis, and having more to do, like the weird, with ' things which do not belong together '. Fisher's adoption of 'hauntology' is of particular interest because it develops from an earlier hostility to Derrida's work which was of a piece with the position of the Cybernetic Culture Research Unit (CCRU), of which Fisher was a member during its existence at Warwick in the late 1990s/early 2000s. This late, phantasmatic reconciliation between Fisher and Derrida is at once intellectually fertile and undeniably poignant.